2022
DOI: 10.1001/jama.2021.23686
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Penetrance of Deleterious Clinical Variants

Abstract: IMPORTANCE Population-based assessment of disease risk associated with gene variants informs clinical decisions and risk stratification approaches. OBJECTIVE To evaluate the population-based disease risk of clinical variants in known disease predisposition genes. DESIGN, SETTING, AND PARTICIPANTS This cohort study included 72 434 individuals with 37 780 clinical variants who were enrolled in the BioMe Biobank from 2007 onwards with follow-up until December 2020 and the UK Biobank from 2006 to 2010 with follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 40 publications
0
48
0
Order By: Relevance
“…Initial penetrance estimates from family-based studies may over-estimate penetrance in the broader population. 209 Another important consideration is that within a given gene, penetrance can vary for different types of variants (eg, truncating variants and missense variants 22 ). As well, factors such as family history and polygenic background can modify penetrance; risk prediction models exist for some hereditary cancers (eg, CanRisk, BOADICEA), which integrate information on monogenic variants, polygenic risk, family history, and other clinical risk factors to provide personalized risk estimates to guide management.…”
Section: Gene-disease Relationships Penetrance and Inclusion On Hered...mentioning
confidence: 99%
See 1 more Smart Citation
“…Initial penetrance estimates from family-based studies may over-estimate penetrance in the broader population. 209 Another important consideration is that within a given gene, penetrance can vary for different types of variants (eg, truncating variants and missense variants 22 ). As well, factors such as family history and polygenic background can modify penetrance; risk prediction models exist for some hereditary cancers (eg, CanRisk, BOADICEA), which integrate information on monogenic variants, polygenic risk, family history, and other clinical risk factors to provide personalized risk estimates to guide management.…”
Section: Gene-disease Relationships Penetrance and Inclusion On Hered...mentioning
confidence: 99%
“…The Gene Curation Coalition (GenCC) database contains information about the validity of gene‐disease relationships 206 . The Clinical Genome Resource (ClinGen) is engaged in ongoing efforts to systematically curate evidence on gene‐disease associations 207,208 . They have found that only a subset of genes commonly included on multigene panels for hereditary breast and ovarian cancer 204 and colorectal cancer and polyposis 205 were supported by strong evidence at the time of the analysis, while others were refuted.…”
Section: Gene‐disease Relationships Penetrance and Inclusion On Hered...mentioning
confidence: 99%
“…Except that a vast majority of genetic mutations may be effects rather than causes of cancer. According to Forrest et al [ 16 ], the chance that a genetic variant (euphemism for mutant) will be linked to a disease diagnosis is relatively low—only about 7%. Therefore, it is expected that there will be many passenger mutations and few driver mutations in a malignant tumor.…”
Section: Genomic Medicinementioning
confidence: 99%
“…Incomplete penetrance is well-recognised for many genetic disorders, and may become the rule rather than the exception, even for rare disorders. 4 As is so often the case with technological advances, the obvious benefits must be balanced against new challenges. In the case of DNA sequencing, the identification of sequence changes in trans does not guarantee a diagnosis, unless the functional significance of these changes can be proven.…”
mentioning
confidence: 99%
“…Conversely, a single clinical entity may be caused by many different genes, for example more than 100 genes have now been linked to the disease that Denis Leigh described as subacute necrotising encephalomyelopathy in 1951, 3 and which is now known as Leigh syndrome. Incomplete penetrance is well‐recognised for many genetic disorders, and may become the rule rather than the exception, even for rare disorders 4 …”
mentioning
confidence: 99%